PENGARUH STRATEGI ORGANISASI, HUBUNGAN PEMASARAN, PEMBELAJARAN ORGANISASI DAN KINERJA TERHADAP KUALITAS LAYANAN (Studi Pada Perguruan Tinggi Swasta Di Jawa Tengah) - Prihatin TP Hutomo (FEB UNTAG Semarang, 2013)
The globalization of markets, rapid advancements in new technology, higher levels of competition, increasing focus on costs and cost management and the inevitable excess of demand over supply in terms of talented individuals all contribute to drive for change contemporary organizations. Models private university than can provide organizations with a robust, integrated and pragmatic approach to anable them to understand the dynamic of the change process and then proactively drive organization change. The main purpose of this research is to test and analyse the direct effect of organizational strategy, marketing relation, organization learning and performance to service quality of management s-1 study program accredited in Kopertis Regional VI Central Java. There are research samples counted 392 respondent students. They are divided into 82 students for A accreditation, and 222 students for B accreditation, and 88 students for C accreditation. The research object is private universities, in this case the accredited management study program. This research took its samples by the techniques purposive random sampling and student met in field. The data analysis is carried out by applying structural equation model. To investigate the difference of service quality based on the accreditation criterion, this research used ANOVA. The research result indicates: 1.Organizational strategy has a direct effect on the marketing relation. 2. Organizational strategy has a direct effect on the service quality. 3. Marketing relation has a direct influence on the organization learning. 4. Marketing relation is influential and negative on the service quality. Negative condition show do not ready study program and lack of preparation of important anticipatory of marketing relation.This is due to the fact that marketing relation has to be applied on broad relations, long-term relation and within study program network and university network based on the vision of the study program service. 5.. Organization learning has a direct effect on performance. Organization learning is street for organization to improve performance reacted precisely to change in environment which do not earn to be forecasted. 6. Organization learning does not have an effect on to service quality. The ability of study program becomes the main focus to gain profit by creating customers satisfaction. 7. Performance has a direct effect on the service quality. 8. There is a different service quality based on the criterion of accreditation.